Estrategias de afrontamiento y nivel de estrés de las enfermeras. Unidad de Cuidados Intensivos de Neonatología - Rosales Velásquez, Minkeli Judith (2023)
The research is quantitative, descriptive, cross-sectional, and aimed to determine the relationship between styles of coping strategies: coping focused on the problem, focused on emotions and other strategies, and the level of work stress in the nurses of the neonatal of the Intensive Care Unit of the Belén Hospital in Trujillo and the Regional Teaching Hospital in Trujillo. The sample universe was 36 nurses who met the inclusion criteria. Two instruments were used: Coping Styles Assessment Scale and Stress Level Assessment Scale, the results were tabulated and presented in single and double entry tables; The Chi-Square Criterion Independence Test (x2) was applied. The results indicate that the most recurrent strategy styles are focused on the problem and focused on emotions in 69.4 percent and 44.4 percent, respectively. The most frequent level of stress in nurses is the low level with 47.2 percent. It is concluded that there is a highly significant relationship between coping styles focused on the problem and focused on emotions with the level of stress in nurses